KEBIJAKAN ASPIRASI DALAM PERSPEKTIF PORK BARREL POLITICS PADA PROGRAM BEASISWA KARTU INDONESIA PINTAR (KIP) KULIAH ASPIRASI HETIFAH DI KOTA SAMARINDA - Awwaliah Maghfirah Suriyani; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2026)
The phenomenon of aspirational policies in practice not only functions as an instrument to meet public needs, but also contains a political dimension that is inseparable from the relationship between people's representatives and constituents. The Kartu Indonesia Pintar (KIP) College Scholarship Program under the Hetifah Aspiration Initiative in Samarinda City serves as an example of a policy that embodies these dynamics. This study aims to analyze how the aspiration policy in the program is carried out as a practice of pork barrel politics in Samarinda City as part of the East Kalimantan constituency. This study uses a qualitative approach with a case study design. Data were obtained through in-depth interviews with documentation and literature studies. The analysis was carried out in a descriptive-analytical manner to reveal the pattern of aid distribution, the role of actors, and the relationship between public policy and political interests. The results of the study show that the KIP-K Aspirasi Hetifah Program not only plays an educational role as an education policy that expands access for underprivileged groups, but also reflects the practice of pork barrel politics. This can be seen from the targeting of certain groups, the linkage with the electoral district, the involvement of political actor networks, and the sustainability of programs that form long-term relationships between legislators and constituents. This program also encourages the formation of political engagement and strengthens the public's positive perception of the performance of the people's representatives. Thus, this policy can be understood as a social instrument as well as a strategy for political representation.